Perbedaan Asupan Lemak, Lingkar Pinggang Dan Persentase Lemak Tubuh Pada Wanita Dislipidemia Dan Non Dislipidemia - Lisya Urip Jati (Jurnal Kesehatan Masyarakat (Undip), 2014)
Differences of fat intake, waist circumference and percentage of bodt fat in dyslipidemia and non dyslipidemia adult women: Heart disease is the leading cause of death in several countries in the world . One of the major risk factors for heart disease is dyslipidemia . Dyslipidemia is a disorder of lipid metabolism characterized by an increase or decrease in plasma lipid fractions . Dyslipidemia has a strong relationship with the occurrence of central obesity . The purpose of this study was to analyze differences in the intake of fat , waist circumference and body fat percentage in dyslipidemia and non dyslipidemia adult women. This research is analytic study with cross sectional approach . The population in this study were adult women who examined their lipid profile in December 2013 in the Clinical Laboratory Cito Indraprasta Semarang . The total sample was 32 people . Independent test analysis of the differences using t-test for variables waist circumference and Mann Whitney test for variable fat intake and body fat percentage to 95 % and a significance level of 5% error. The results showed 17 adult women ( 53.1 % ) and 15 female adult dyslipidemia ( 46.9 % ) non- dyslipidemia. Average intake of fat, waist circumference and percentage body fat in adult women dyslipidemia higher than non dyslipidemia in adult women. Analysis of statistical tests showed difference in fat intake , waist circumference and body fat percentage in women adult dyslipidemia and non dyslipidemia (p value, respectively p = 0.002, p = 0.0001 and p = 0.0001)